A questão da intencionalidade em Husserl e Heidegger: caminhos e descaminhos - Lauer, Luís Felipe Netto (2008)
The conductive thread of Edmund Husserl and Martin Heidegger s phenomenological investigations is the concept of intentionality; his analysis has for purpose to solve the fundamental methodological problem concerning the scientific disclosure of the sphere of lived experience (Erlebnis). So that it becomes clear, it is necessary to consider him formally. In Husserl, the sphere of lived experience is the one of the pure ego or pure consciousness, and the intentionality is understood as intentionality of consciousness; in Heidegger, it is treated of what denominated factical life or existence of Dasein, in that the intentionality designates the type of comportment that the human existence maintains in relation to itself and to the world. This work seeks a critical confrontation among the two positions, pointing out the heideggerian concern with the inadequacies of the theoretical attitude and her form of conceiving the field of the formal, towards an investigation concerning the nature and the formation of the concepts and philosophical statements as formal indications.